Pengaruh Pemberian Jinten Hitam terhadap Produksi Asi pada Ibu Menyusui - Yuni Sulistiawati; Nur Apriyanti (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The purpose of this study was to determine the effect of giving black cumin on breast milk production in breastfeeding mothers at the Adirejo Health Center, East Lampung Regency in 2021. Research methodology: The type of research used is quantitative with a quasi-experimental research design and using a posttest only design approach with a control group Results: The results of this study indicate that the average volume of breast milk after being given black cumin is 173.61 ml. The average volume of breast milk in the control group was 122.5 ml and the independent sample t-test test obtained p value 0.000. Limitations: In this study, it did not look at convonding factors that affect milk production such as psychological conditions and anxiety levels of postpartum mothers Contribution: The results of this study are expected to be used as input for health workers at the Adirejo Health Center, East Lampung Regency in an effort to provide black cumin to help launch breast milk production in postpartum mothers.